Lead-free bismuth glass system towards eco-friendly radiation shielding applications - Alzahrani, Jamila S.; Sriwunkum, Chahkrit; Tonguc, Baris Tamer; Alothman, Miysoon A.; Olarinoye, I. O.; Al-Buriahi, M. S. (Elsevier, 2023)
In this study, the gamma-ray photon, electron, proton, helium ion, carbon ion, thermal neutron, and fast neutron interaction parameters of the (70-x)(Bi2O3 + ZnO) + x(V2O5 + TeO2) + 20B(2)O(3) + 6.5SiO(2) + 2.5Al(2)O(3) + 1(CeO2 + Sb2O3) glass system were estimated with the aim of assessing their radiation shielding potentials. The mass attenuation coefficients (MACs) of the glasses were estimated for photon energies between 0.015 and 15 MeV using the PHITS simulation code and XCOM software. The stopping powers of charged radiation such as electrons, protons, alpha-particles, and carbon ions were also estimated by Monte Carlo simulation of particle transport using PHITS. The narrow beam transmission simulated using PHITS yielded values of MAC that were not so different from those from XCOM. The MACs of B/V-ZBVSA1 vary from 0.039-90.747 cm(2)/g, while those of B/V-ZBVSA2, B/V-ZBVSA3, and B/V-ZBVSA4 vary from 0.035-69.724, 0.036-73.088, and 0.037-70.597 cm(2)/g, respectively. The HVL of the glasses varied from 0.011-2.56 cm, 0.019-3.69 cm, 0.017-3.31 cm, and 0.017-3.36 cm for B/V-ZBVSA1 - B/V-ZBVSA4, respectively The effective atomic number varied within the limits: 28.36-76.06, 19.67-67.91, 22.14-68.70, and 22.39-68.08 for BV-ZBVSA1 - BV-ZBVSA4, respectively. The stopping powers (S-p) of electrons in BV-ZBVSA1, BV-ZBVSA2, BV-ZBVSA3, and BV-ZBVSA4 were in the range 1.219-8.043 MeVcm(2)/g, 1.295-9.306 MeVcm(2)/g, 1.264-8.859 MeVcm(2)/g, and 1.257-8.793 MeVcm(2)/g correspondingly. Comparatively, the S-p of protons, alpha-radiation, and carbon ions follows the order: BV-ZBVSA2 > BV-ZBVSA3 > BV-ZBVSA4 > BV-ZBVSA1. Also, the value of Sigma(R) for BV-ZBVSA1, BV-ZBVSA2, BV-ZBVSA3, and BV-ZBVSA4 was 0.1171, 0.1126, 0.1133, and 0.1103 cm(-1) accordingly, while the corresponding total cross-section of thermal neutrons was 67.6227, 46.8356, 59.1179, and 56.6994 cm(-1). The present glasses showed superiority in absorbing photons and neutrons compared to some existing shields and previously recommended glasses. The present glassy samples, thus, can be adopted for radiation protection purposes, among others in radiation facilities.
Keywords: Shielding materials; Radiation interaction; Glasses; Charged radiation; Neutrons